Screening of Oenological Yeasts for Volatile Phenol Release in Smoke-exposed Red Wine - Zieff, D.; du Toit, M.; Schneider, R.; Divol, B. (South African Journal of Enology and Viticulture, 2025)
The frequency of wildfires has increased over the past few years, particularly in winemaking countries. This is partly because of climate change, thereby elevating the risk of producing smoke-tainted wines. The off-flavours associated with smoke taint originate from volatile phenols, which are progressively liberated from their glycosylated precursors during the winemaking process. Current strategies to prevent and/or mitigate the negative impact of smoke taint in wine production are not fully effective because it is difficult to remove glycosylated volatile phenols without affecting wine quality. One ill-explored avenue could be to use wine yeasts with extracellular glycosidase activities in combination with other downstream remediation processes. For this study, grape juice was obtained from smoke-exposed Pinotage grapes. Thirty yeast strains were screened for their potential to release volatile phenols. Partial fermentations were conducted on laboratory scale for 96 h, after which volatile phenols were quantified using GC-MS. A large variation was observed between yeast strains in their ability to liberate volatile phenols, particularly guaiacol, which serves as a key indicator of smoke taint in wine. Most strains released guaiacol at levels above its detection threshold in wine (23 μg/L). Nevertheless, Lachancea thermotolerans IWBT Y940, Starmerella bacillaris IWBT Y550 and Wickerhamomyces anomalus IWBT Y541 displayed the highest total volatile phenol release in smoked Pinotage, close to that observed with a commercial glycosylase formulation.